2010
DOI: 10.1111/j.1471-4159.2010.06980.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of adenosine and wake‐promoting basal forebrain in insomnia and associated sleep disruptions caused by ethanol dependence

Abstract: J. Neurochem. (2010) 115, 782–794. Abstract Insomnia is a severe symptom of alcohol withdrawal; however, the underlying neuronal mechanism is yet unknown. We hypothesized that chronic ethanol exposure will impair basal forebrain (BF) adenosinergic mechanism resulting in insomnia‐like symptoms. We performed a series of experiments in Sprague–Dawley rats to test our hypothesis. We used Majchrowicz’s chronic binge ethanol protocol to induce ethanol dependency. Our first experiment verified the effects of ethanol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(99 citation statements)
references
References 76 publications
(138 reference statements)
3
96
0
Order By: Relevance
“…[55][56][57][58][59] The recent studies by Thakkar and coworkers strongly suggest that alcohol-induced increase in adenosine in the basal forebrain and stimulation of A 1 receptors in the cholinergic neurons of the corticopetal basal forebrain arousal system is particularly involved in the acute somnogenic effects of alcohol. [60][61][62] First, they showed with in vivo microdialysis that local perfusion of alcohol elevates significantly the extracellular concentration of adenosine in the basal forebrain. 60 Second, systemic alcohol administration reduced the activity of cholinergic cells in the basal forebrain and the bilateral microinjection of an A 1 receptor antagonist in the same brain region significantly attenuated alcohol-induced sleep.…”
Section: Adenosine As a Mediator Of The Psychostimulant Effects Of Camentioning
confidence: 99%
“…[55][56][57][58][59] The recent studies by Thakkar and coworkers strongly suggest that alcohol-induced increase in adenosine in the basal forebrain and stimulation of A 1 receptors in the cholinergic neurons of the corticopetal basal forebrain arousal system is particularly involved in the acute somnogenic effects of alcohol. [60][61][62] First, they showed with in vivo microdialysis that local perfusion of alcohol elevates significantly the extracellular concentration of adenosine in the basal forebrain. 60 Second, systemic alcohol administration reduced the activity of cholinergic cells in the basal forebrain and the bilateral microinjection of an A 1 receptor antagonist in the same brain region significantly attenuated alcohol-induced sleep.…”
Section: Adenosine As a Mediator Of The Psychostimulant Effects Of Camentioning
confidence: 99%
“…NGF mediates higher brain functions such as learning and memory and the findings from this work raises the concern that persistent AAS use in humans may affect those mechanisms that lie at the core of neuronal plasticity (the brain's ability to reorganize itself by forming new neural connections across a person's life-span). Given the importance of the basal forebrain in producing acetylcholine which plays a key role in the ability of brain cells to transmit information to one another [33] and the role the hippocampus plays in memory consolidation [34], it is feasible that the memory deficits observed in previous work and in the current study may reflect damage caused to brain plasticity in humans who use AAS. However, further work on the potential interaction between persistent AAS use, brain plasticity and memory deficits in human populations is clearly needed before any firm conclusions can be reached.…”
Section: Discussionmentioning
confidence: 84%
“…Whereas most studies reported a transient increase of A 1 R agonist binding upon acute or chronic administration of ethanol, one old [95] and one recent [125] study reported decreases of A 1 R expression in some brain areas of rats. Decreased A 1 R expression in the wake-promoting basal forebrain may be related to insomnia associated with ethanol withdrawal [125].…”
Section: Effects Of Ethanolmentioning
confidence: 97%